Efisiensi Investasi: Peran Kunci Struktur Kepemilikan, Debt Maturity, dan Kualitas Laporan Keuangan - Nurina, Lia; Marjono, Marjono; Napiajo, Napiajo (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2025)
This study examines the key factors influencing investment efficiency, focusing on ownership structure, debt maturity, and financial reporting quality. Using a quantitative approach, the research analyzes data from 102 energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The results indicate that institutional ownership and managerial ownership have a positive and significant impact on investment efficiency, aligning with agency theory by reducing information asymmetry and aligning interests between managers and shareholders. Conversely, debt maturity shows a negative and significant effect, suggesting that short-term debt acts as a disciplinary mechanism to curb overinvestment. Financial reporting quality also positively influences investment efficiency, though its impact is relatively weaker. These findings highlight the importance of robust corporate governance mechanisms, optimal debt structuring, and transparent financial reporting in enhancing investment efficiency. The study contributes to the literature by providing empirical evidence from the energy sector in an emerging market context and offers practical recommendations for companies and policymakers.